Resilience, Post-Traumatic Growth, and Psychological Well-Being Among Adolescents Experiencing Parents’ Marital Dissolution - Daniswara Agusta Wijaya; Endang Widyorini; Emiliana Primastuti; Jemerson Dominguez (Jurnal Ilmu Perilaku, 2021)
The marital dissolution as a traumatic event for children and adolescents might yield different outcomes for each adolescent. Previous studies suggested that adolescents who have high resilience tend to experience positive changes / post- traumatic growth following traumatic events, which results in higher well-being. Hence, it is necessary to conduct research about resilience and post-traumatic growth as predictors of psychological well-being among adolescents who have been through their parents’ marital dissolution. The recent study aims to investigate the relations among those variables. A total of 56 participants (mean age: 15.27; 66.1% female) who lived in Semarang completed three measurements. Correlational, t-test, and path analysis were applied. The result suggests that both resilience and post-traumatic growth significantly and positively correlated toward psychological well-being. Furthermore, post-traumatic growth was found to have a significant partial mediating effect on the relationship between resilience and psychological well-being. These findings suggest that though promoting resilience could improve the psychological well-being of adolescents who have been through their parents’ marital dissolution, clinicians need to ensure that adolescents experience post-traumatic growth through cognitive therapy or counseling sessions to achieve better psychological well-being.